Kontribusi Pemuda Kristen dalam Mencegah Penyebaran Ideologi Radikalisme Melalui Media Sosial - Omega Bia; Ivony Welchristin Adelis Oematan; Yakobus Adi Saingo (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The ideology of religious radicalism poses a serious threat that can disrupt social peace, particularly for the younger generation who are more vulnerable to being exposed to radical ideas. Religious radicalization, as a form of extremism, has the potential to disturb interfaith harmony and create social tensions. Therefore, preventing the spread of this ideology is crucial, one of which can be achieved through the involvement of Christian youth in utilizing social media. Social media has become a highly effective platform for spreading various types of information, both positive and harmful. As such, Christian youth play a very important role in addressing this threat. This research aims to examine the contribution of Christian youth in preventing the spread of religious radicalism ideology through social media. The approach used is qualitative with a literature study, where data is obtained from various relevant scholarly sources. The results of the study show that Christian youth can use social media as a tool to spread messages of peace, tolerance, and inclusivity. This is important in fostering harmony amidst religious diversity in Indonesia. Christian youth can play an active role by correcting the misconceptions often propagated by radical groups. By spreading positive and constructive messages, Christian youth can help society become more discerning in filtering information, thus reducing the potential spread of hatred. Through their involvement on social media, Christian youth have significant potential in strengthening interfaith harmony and creating a more peaceful and harmonious social environment.